ANALYSIS OF STUDENTS’ RESPONSES TO GAME-BASED LEARNING METHODS ON MOTION AND FORCE TOPIC - Putri, Dina Rizkia (SEMESTA: Journal of Science Education and Teaching, 2024)
The purpose of this research is to find out whether the game based learning method presented can be well received or not by students. Respondents in this study were 30 seventh grade students. The data collection technique used in this study was a student response questionnaire. The results of the data obtained and analyzed qualitatively descriptive and assisted by Microsoft Excel application on Windows. Based on the results of the student response questionnaire to the Game Based Learning learning method, the average percentage is 88% and is in the very good category. So it can be concluded that game based learning method gets a very good response from students.